Assessment of the Results of Mexico's Agro-export Sector Amid the COVID-19 Pandemic in 2020 (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2020)
Amid the COVID-19 pandemic that swept through humanity, the Mexican government decided to halt all economic activities that would limit the spread of infections. Many of them were affected; however, agricultural product exports have shown a surplus in the trade balance. How is this increase in economic activity explained when a generalized crisis in productive activity has been forecasted? The primary sector is a sector of prime necessity that maintains or increases the demand for products even in the face of people's inactivity as they shelter in their homes and require sustenance. The objective of this documentary research is to illustrate the prevailing situation of the agro-export sector in the face of the challenging situation caused by the global pandemic in 2020.